The Effectiveness of Social Media in Learning English Autodidactically - Surgawie S; Ibrahim Manda; Sitti Aisa; Isumarni; Sam Hermansyah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study explores the effectiveness of social media as a tool for autonomous English learning. Employing a descriptive qualitative approach, data were gathered through interviews with five seventh-semester students from the Indonesian Language Education program at Muhammadiyah Sidenreng Rappang University. The research investigates whether social media facilitates self-directed English learning and contributes to skill enhancement. The findings reveal that students perceive social media as an effective platform for independent English learning when used strategically. Platforms such as YouTube, Instagram, and TikTok provide diverse learning resources, including video-based lessons and interactive content, which support vocabulary development, pronunciation improvement, and overall language proficiency. However, challenges such as the lack of structured guidance, potential distractions, and difficulties in tracking progress were also noted. This study underscores the potential of social media as a supplementary tool for autonomous English learning, highlighting the need for strategic and disciplined use to maximize its benefits.